2004
DOI: 10.1099/jmm.0.45657-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of normal microbiota on some aspects of the immune response during experimental infection with Trypanosoma cruzi in mice

Abstract: To study the influence of normal associated microbiota on systemic immunological responses during experimental Chagas' disease, germ-free and conventional NIH Swiss mice were infected with Y strain of Trypanosoma cruzi. Although no statistical differences in mortality and parasitaemia were found, conventional mice showed IFN-ª, TNF-AE and NO production (P , 0 . 05) by spleen cell cultures and higher blood levels of immunoglobulins of the IgG2a isotype (P , 0 . 05) when compared to their germ-free counterparts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Our results showed that germfree mice died much earlier after bacterial infection, whereas conventional animals, which are capable of inflaming in response to the bacterial challenge, survived for .3 d. Our results are in agreement with others, which demonstrated the increase of susceptibility to parasite infection in absence of commensal microbiota. For example, germ-free mice have decreased capacity to deal with Leishmania major (24) and Trypanosoma cruzi infections (25). Altogether, these experiments in germfree mice would suggest that the ability to inflame in response to bacteria, and possibly other parasites, is evolutionarily relevant.…”
Section: Discussionmentioning
confidence: 82%
“…Our results showed that germfree mice died much earlier after bacterial infection, whereas conventional animals, which are capable of inflaming in response to the bacterial challenge, survived for .3 d. Our results are in agreement with others, which demonstrated the increase of susceptibility to parasite infection in absence of commensal microbiota. For example, germ-free mice have decreased capacity to deal with Leishmania major (24) and Trypanosoma cruzi infections (25). Altogether, these experiments in germfree mice would suggest that the ability to inflame in response to bacteria, and possibly other parasites, is evolutionarily relevant.…”
Section: Discussionmentioning
confidence: 82%
“…First, colonization by commensal microorganisms is key to immune development. [9][10][11][12] Second, the commensal community keeps in check invading pathogens and prevents them from expressing virulence. 13,14 Third, the intestinal microbiota appears to digest glycans and regulate fat storage in mice and potentially in humans.…”
Section: Gut Microbiota Health and Diseasesmentioning
confidence: 99%
“…Their importance has been demonstrated in numerous clinical studies and by using animal models, which show that disruption of host-commensal interactions is associated with a variety of diseases and conditions (1,2,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). These include cancer (8), chronic intestinal inflammation (12,15), autoimmunity (14), and increased susceptibility to infection by bacteria, viruses, and parasites, both in the intestine and at extraintestinal sites (1,4,(16)(17)(18)(19)(20)(21)(22)(23)(24). An underlying principal emerging from these studies is that the commensal microbiota is a major regulator of host immune function, and it is the disruption of this interaction that underlies many of these conditions.…”
mentioning
confidence: 99%